Oxide-stabilized microstructure of severe plastically deformed CuCo alloys - Stückler, Martin; Zálešák, Jakub; Müller, Timo; Wurster, Stefan; Weissitsch, Lukas; Meier, Martin; Felfer, Peter; Gammer, Christoph; Pippan, Reinhard; Bachmaier, Andrea (Journal of Alloys and Compounds, 2022)
Nanocrystalline materials are well known for their beneficial mechanical and physical properties. However, it is of utmost importance to stabilize the microstructure at elevated temperatures to broaden the window of application e.g. by pinning grain boundaries through impurities or oxides. CuCo alloys, severe plastically deformed using high-pressure torsion, were used to investigate the evolution of oxides upon annealing. These investigations were performed using electron microscopy, synchrotron high-energy X-ray scattering and atom probe tomography. Monitoring the evolution of oxides by in-situ small angle scattering investigations indicates the growth of primary oxides as well as the formation of another species of oxide at elevated temperatures. Slightly different coarsening can be observed in heat-treated samples, which can be traced back to the influence of different oxide amounts. The initially supersaturated CuCo matrix changes by the decomposition process as well as Co- and Cu-based oxides formation and growth. It has been found that the major number of oxides which are present after annealing, can already be found in the starting materials.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Atom probe tomography; High-pressure torsion; Nanocrystalline material; Severe plastic deformation; Small-angle X-ray scattering; Supersaturation

Revealing the γ′ and γ″ Phase Fractions of Additively Manufactured and Differently Heat-Treated Nickel-Base Superalloy IN718 by Atom Probe Tomography and Their Impact on Mechanical Properties - Volpato, Guilherme; Vollhüter, Jan; Diepold, Benedikt; Meier, Martin; Pröbstle, Martin; Göken, Mathias; Niendorf, Thomas; Felfer, Peter; Neumeier, Steffen (Advanced Engineering Materials, 2024)
Powder bed fusion using a laser beam (PBF-LB) has great potential for the production of geometrically complex industrial components, allowing for unprecedented geometrical optimization and freedom of design. This potential is particularly relevant in the case of turbine components, whose microstructure and properties are directly affected by the extreme PBF-LB processing conditions. In this context, this study aims to investigate the impact of PBF-LB on the microstructure and mechanical behavior of Inconel alloy 718 (IN718) when heat treated according to different sequences. Atom probe tomography is used to analyze the composition, morphology, configuration, and volume fraction of γ′ and γ″ precipitates as a function of heat treatment conditions. Their impact on the material is evaluated using compression tests under different build orientations. It is shown that when PBF-LB IN718 is subject to solution annealing at 930 °C and subsequently aged, δ needles form in its microstructure at the expense of γ′ and γ″, thus reducing mechanical strength. Such is not the case when the solution annealing step is omitted or when its temperature is increased to 1000 °C, conditions whose superior mechanical behavior have been attributed to a high dislocation density and a large volume fraction of aging phases, respectively.
CRIS-Team Scopus Importer:2025-02-04
Keywords: atom probe tomography; Inconel 718; Ni-base superalloys; precipitation behavior; selective laser melting